MENINGKATKAN LITERASI BUDAYA DAN KEWARGANEGARAAN SISWA KELAS IV MELALUI MEDIA MODUL KliK PADA PEMBELAJARAN PKN - Siti Anzani , Amalia; Muhammad Fahri; Kasman , Rusdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Civics lessons play a very important role in character building and understanding the rights and obligations of students as citizens. In this 21st century era, the integration of literacy, especially cultural and civic literacy, is important in Civics learning in elementary schools. However, the low understanding of Civics material due to limited learning media, the lack of interaction and literacy reinforcement in the learning process, and the lack of effective evaluation are obstacles in improving cultural and civic literacy. The Creative Literacy Class Module (KLiK) developed by Sekolah Literasi Indonesia (SLI) is a solution through creative and systematic literacy activities in the learning process. This study aims to determine the effectiveness of the KLiK Module in improving cultural and civic literacy of grade 4 elementary school students through the Kemmis and Mc Taggart model of classroom action research. The results of this study showed an increase in student literacy after the use of the KLiK Module, exceeding the target of completeness. Students better understand gotong royong, are able to relate to Pancasila values, and are more active in the learning process. Based on these findings, it is recommended that teachers utilize the KLiK Module, students are encouraged to be more proactive, schools support the provision of literacy-based learning media, and future researchers can refine and expand this research